Novel method for the determination of water content and higher heating value of pyrolysis oil - Mohammed, I.Y. (North Carolina State University, 2015)
This research provides a novel approach for the determination of water content and higher heating value of pyrolysis oil. Pyrolysis oil from Napier grass was used in this study. Water content was determined with pH adjustment using a Karl Fischer titration unit. An equation for actual water in the oil was developed and used, and the results were compared with the traditional Karl Fischer method. The oil was found to have between 42 and 64 moisture under the same pyrolysis condition depending on the properties of the Napier grass prior to the pyrolysis. The higher heating value of the pyrolysis oil was determined using an oil-diesel mixture, and 20 to 25 wt of the oil in the mixture gave optimum and stable results. A new model was developed for evaluation of higher heating value of dry pyrolysis oil. The dry oil has higher heating values in the range between 19 and 26 MJ/kg. The developed protocols and equations may serve as a reliable alternative means for establishing the actual water content and the higher heating value of pyrolysis oil.